2018
DOI: 10.7717/peerj.4792
|View full text |Cite
|
Sign up to set email alerts
|

Association of epilepsy and asthma: a population-based retrospective cohort study

Abstract: BackgroundEpidemiologic data supporting the epilepsy–asthma association are insufficient. Therefore, we examined this association in this study.MethodsBy using claims data from the National Health Insurance Research Database (Taiwan), we executed a retrospective cohort analysis. Analysis 1 entailed comparing 150,827 patients diagnosed as having incident asthma during 1996–2013 with disease-free controls who were selected randomly during the same period, frequency matched in terms of age and sex. Similarly, ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Previous studies among US children aged 0-17 years reported that the lifetime prevalence of asthma was related to a higher risk of epilepsy (2.30 [1.50-3.52]) ( 8 ). Similarly, a recent cohort study including 150,827 asthma patients showed that the asthma patients had an increased risk of epilepsy than health controls (hazard ratio=1.39) ( 9 ). All these findings indicated that asthma was associated with the risk of epilepsy, which was consistent with the results of our MR study based on data from the ILAEC and FinnGen Consortium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies among US children aged 0-17 years reported that the lifetime prevalence of asthma was related to a higher risk of epilepsy (2.30 [1.50-3.52]) ( 8 ). Similarly, a recent cohort study including 150,827 asthma patients showed that the asthma patients had an increased risk of epilepsy than health controls (hazard ratio=1.39) ( 9 ). All these findings indicated that asthma was associated with the risk of epilepsy, which was consistent with the results of our MR study based on data from the ILAEC and FinnGen Consortium.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, two previously published population-based studies of adults revealed that patients with epilepsy were often accompanied by physical comorbidities such as asthma ( 6 , 7 ). In addition, numerous case-control studies have announced that the prevalence of asthma was related to higher odds of epilepsy either in children ( 8 ) or in adults ( 9 ). These data suggest that asthma might be associated with high susceptibility to epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is associated with multiple neuropsychiatric disorders in children and adults, some of which are anxiety, attention deficit hyperactivity disorder, autism, and depression. Interestingly, the retrospective cohort analysis of 150,827 patients demonstrated that Asthma may be associated with high epilepsy risk, and epilepsy may be associated with high asthma risk among children [28]. Proinflammatory cytokines play neuromodulatory functions, in addition to contributing to aberrant neuronal excitability underlying seizure disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Other commonly diagnosed comorbidities in epilepsy include migraine, cardiovascular diseases, stroke, respiratory diseases (e.g., asthma), gastrointestinal conditions, allergies, bone diseases, and increased premature mortality [33,[63][64][65][66][67][68][69][70][71]. Diabetes represents another comorbidity, with epilepsy patients being at a higher risk of contracting diabetes and adverse postdiabetes outcomes [72].…”
Section: Comorbidities In Epilepsymentioning
confidence: 99%